AB1120 Juvenile dermatomyositis: A MRI scoring system to assess acute inflammation and damage. (23rd January 2014) - Breton, S.; Lambot, K.; Elie, C.; Quartier, P.; Wouters, C.; Gitiaux, C.; Bodemer, C.; Brunelle, F.; Bader-Meunier, B.
Abstract : Background: Magnetic Resonance Imaging (MRI) is a very sensitive method to demonstrate muscle inflammation, but there is no standardized scoring system to assess both inflammation and damage in juvenile dermatomyositis Objectives: To propose and to validate a MRI scoring system assessing acute inflammation and damages findings in Juvenile Dermatomyositis (JD). Methods: Children with JD referred to our institution for proximal thighs MRI between 1998 and 2009 were retrospectively included. The MRIs were analysed twice by two musculoskeletal paediatric radiologists with a 6 weeks interval. Inflammatory activity was scored including muscle œdema (0=none, 1=mild and 2=severe), fascial, subcutaneous fat and skin œdema (qualitative scale). Damages were scored including calcinosis in muscles, fascias, subcutaneous fat and skin (qualitative scale), muscle and fat atrophy (qualitative scale) and muscle fatty infiltration (0=none, 1=mild and 2=severe). Results: 20 children were included (median age, 7.1 years; range, 1-15; 6 boys and 14 girls). 45 MRI were analysed, which 10 were performed in the 2 months diagnosis. The most common MRI findings were muscle œdema (80%) regarding inflammatory activity, and muscle fatty infiltration (24%) regarding damages. Both intra- and inter-observers agreements were excellent regarding global score (Intraclass Correlation Coefficient [ICC], from 0.95 [CI 95%, 0.87-0.98] to 0.97 [0.94-0.99] and 0.88 [0.74-0.95], respectively). Inter-observer ICC were also excellent regarding inflammatory and damage subscores (0.84 [0.73-0.91] and 0.89 [0.66-0.97], respectively). Conclusions: MRI is a reliable and reproductible tool for analysing inflammatory activity and damage during JD. Disclosure of Interest: None Declared